Measurement of the polarization profile across a surface-stabilized ferroelectric liquid crystal cell using the pyroelectric laser-intensity-modulation method - VIJ, JAGDISH KUMAR (American Institute of Physics, 2003)
The pyroelectric technique, called the laser-intensity-modulation method, was used for investigations of the spatial distribution of the pyroelectric coefficient that gives information about the director profile in ferroelectric liquid crystal (FLC) cells. The pyroelectric current from a cell, illuminated by the intensity-modulated laser beam, was measured as a function of the modulation frequency. The Tikhonov regularization procedure was used for the deconvolution of the pyroelectric current spectrum into the spatial profile of the pyroelectric coefficient. It was found that in the surface-stabilized ferroelectric liquid crystal (SSFLC) structure with a splayed director profile, the flexoelectric contribution to the local polarization has comparable magnitude with the spontaneous one. The effective flexoelectric coefficient of the investigated FLC material and the flexoelectric polarization of the SSFLC structure were determined.
PUBLISHED
Keywords: Electronic & Electrical Engineering